Cardiovascular disease burden in adult patients with cancer: An 11-year nationwide population-based cohort study. (15th October 2020) - Youn, Jong-Chan; Chung, Woo-Baek; Ezekowitz, Justin A.; Hong, Jung Hwa; Nam, Hyewon; Kyoung, Dae-Sung; Kim, In-Cheol; Lyon, Alexander R.; Kang, Seok-Min; Jung, Hae Ok; Chang, Kiyuk; Oh, Yong-Seog; et al.
Abstract: Background: Cardiovascular disease (CVD) is an important cause of morbidity and mortality in patients with cancer. However, the real-world CVD burden of adult cancer patients has not been well established. This study aimed to evaluate the prevalence and mortality of pre-existing and new-onset CVD in patients with cancers. Methods: We analysed the prevalence and mortality of pre-existing and new-onset CVD in 41, 034 adult patients with ten common solid cancers in a single payer system using data from the Korean National Health Insurance Service-National Sample Cohort from 2002 to 2013. Results: When all types of cancer were included, 11.3% ( n = 4647) of patients had pre-existing CVD when they were diagnosed with cancer. After excluding patients with pre-existing CVD, 15.7% of cancer patients ( n = 5703) were newly diagnosed with CVD during the follow-up period (median 68 months). Both pre-existing and new-onset CVD were associated with increased risk of overall mortality and 5-year mortality. Multivariate analysis to predict all-cause mortality indicated both pre-existing and new-onset CVD, male sex, old age, prior history of diabetes or chronic kidney disease, suburban residential area, and low-income status as significant factors. Conclusions: Eleven percent of cancer patients had pre-existing CVD at the time of cancer diagnosis, and about 16% of cancer patients without pre-existing CVD were newly diagnosed with CVD, mostly within 5 years after the cancer diagnosis. Proper management of pre-existing CVD is necessary and pre-emptive prevention of new-onset CVD may alter treatment options and outcomes. Highlights: Eleven percent of patients had pre-existing CVD at the time of cancer diagnosis. Sixteen percent of cancer patients were newly diagnosed with CVD. After excluding cancer-related death, CVD was the most common cause of death. New-onset CVD is strongly associated with mortality in cancer patients. Proper management of pre-existing CVD and prevention of new-onset CVD are important.